Adjusting The Academic Integrity’s Atmosphere among Medical Students: An Exploratory Study - Armyanti, Ita; Arundina Triharja Tejoyuwono, Agustina; Asroruddin, Muhammad; Ishan, Zulfa Khairunnisa (Universitas Gadjah Mada, 2025)
Background: The academic integrity known as part of academic culture and consist of moral values that having relationship with medical professionalism. The academic integrity term is more easily recalled through academic misconduct. The academic misconduct during medical school were the main predictor as they becoming future medical doctor. Aims: to explore the medical students and teachers’ perceptions about the academic integrity and academic honestyMethods: The phenomenology approach conducted and eighteen respondents involved in four focus group discussion and five respondents in in-depth interviews separately. Data analysed using thematic analysis, using the steps for coding and theorization method.Results: Two main themes were identified; the academic integrity and shaping medical professionalism through academic honesty. The issue of academic misconduct and dishonesty were emerged, in line with the negativity bias theory. Conclusion: It is our collective homework as medical teacher and me managers, to develop appropriate learning model for each medical school.